Strategi Pusat Kajian Perempuan Solo dalam Memberikan Edukasi mengenai Pendidikan Seksualitas pada Remaja di Kota Surakarta - Amaliya, Zira Naily; Trinugraha, Yosafat Hermawan; Pudyastuti, Septina Galih (Universitas Mathla'ul Anwar Banten, 2024)
Teenager are in transitional period that requires appropriate information according to their needs and changes they experience regarding sexuality issues. Problems found in the field such as sexual violence, early marriage, unwanted pregnancy, and taboo perceptions about sexuality issues are the background of the importance of comprehensive sexuality education. The solo women's study center as one of the communities actively engaged in educating teenagers about the importance of sexuality education by considering the Comprehensive Sexual Education curriculum with the aim of increasing knowledge, making preventive efforts, and providing a safe space for adolescents. This research method uses a qualitative approach with a case study type, data collection techniques using in-depth interviews, participatory observation, and documentation. The data that has been obtained is then tested for credibility using source triangulation, then analyzed using liberal feminist theory. The results showed that the strategies carried out by PUKAPS such as sea-project, femstride class, femstride safer space project, making the film “Payung Dara”, campaigning through social media, and advocacy services have a positive influence on the fulfillment of reproductive rights and the improvement of more inclusive sexuality education.